Global stratospheric methane loss from satellite observations - Qiang Fu; Cong Dong (Proceedings of the National Academy of Sciences, 2026)
Stratospheric CH 4 oxidation represents both an important sink in the global CH 4 budget and a major source of stratospheric water vapor and hydrogen radicals, exerting strong influences on global climate and ozone chemistry. Yet, the magnitude of stratospheric CH 4 chemical loss remains highly uncertain, with previous estimates largely relying on chemistry-climate models (CCMs). Here, we present an observationally based estimate of stratospheric CH 4 loss ( L STR ), derived from the CH 4 diabatic flux across the isentropic surface fitted to the tropical tropopause, using satellite measurements of CH 4 concentration, temperature, and radiative heating rates for 2007–2010. We obtain an L STR of 49.8 ± 7.8 Tg/y, compared with 38.1 Tg/y estimated from reanalysis, and 25.7 Tg/y (range: 19.6 to 35.9 Tg/y) derived from CCMs, indicating that both reanalysis and CCMs systematically underestimate stratospheric CH 4 loss. We show that discrepancies in global CH 4 diabatic fluxes from the reanalysis and CCMs, when compared with observations, are mainly driven by biases in CH 4 concentrations and further enhanced by errors in temperature and radiative heating. Substituting our observational estimate for the model-based stratospheric loss in the bottom-up global CH 4 budget reduces the reported imbalance for the 2000s from 23 to 3 Tg/y, bringing it into close agreement with the 5 Tg/y (range: −4 to 13 Tg/y) imbalance inferred from top-down estimates. These findings highlight the critical role of observational constraints on L STR in reconciling the global CH 4 budget. They also carry important implications for understanding stratospheric water vapor and ozone chemistry.